PENGARUH POSISI DEPARTEMEN TEKNOLOGI INFORMASI, VISI MISI PERUSAHAAN, DAN LATAR BELAKANG DEWAN DIREKSI TERHADAP KELENGKAPAN PENGUNGKAPAN INTERNET FINANCIAL REPORTING - , Hetin Tridayani ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to examine the effect of information technology department position, vision and mission of the company, and the background of board of directors towards the comprehensiveness of Internet Financial Reporting revealment that measured by using index revealing IFR. As stated by theory to be based on resource, that resource and ability of the company is the central consideration in formulating the strategy. Therefore the company also investigates resource and IT ability in a special department that is information technology department to fulfill the strategy of IFR revealment. This research also investigates what vision and mission of the company related IT having strategy attainment of revealing IFR completely. Moreover, this research also examine the background of board of directors that having education characteristic and experience related with IT in improving board of directors roles to optimize financial information revealment completely through IFR. This research investigates the certain companies that become the member in Indonesian Capital Market (BEI) period 2008-2010. Result of the research showed that IT department position affecting significant positive toward comprehensiveness of IFR revealment. Thus can be concluded that the more high position level of IT department on the structure organization of the company so the more high the comprehensiveness of IFR revealment conducted by the company. Examining the effect of vision and mission of the company related with IT to the comprehensiveness of IFR revealment indicates non-significant result. Finally, multiple regression tests over the effect of the board of directors background to the comprehensiveness of IFR revealment indicates significant result.